Inflation, stabilization, growth in Argentina : a CGE approach : economic successes and problems under the convertibility law - Wang, Baotai (Economía. Seminarios, 1995)
This paper reports the results of simulation experiments which were conducted by using a CGE model of Argentina. The results suggest that: the economy could not have been stabilized by using the preannouneed devaluation rate during 1978-81; economic perfor- mance could have improved in 1985-89 under a modified Austral plan but, with the altered structure, there would still be a severe currency appreciation; and the Convertibility Law based programme is very successful in arresting inflation and eliminating a budget deficit, though it is not free from side effects such as money supply shortages and high interest rates.